PROFIL PENGKAJIAN EARLY WARNING SCORE (EWS) DI INSTALASI GAWAT DARURAT RSU SIAGA MEDIKA PURBALINGGA - Wilastri, Eti; Siwi, Adiratna Sekar; Sumarni, Tri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Emergency conditions require prompt and appropriate treatment to prevent clinical deterioration. The Early Warning Score (EWS) is a tool used to monitor vital signs and support early detection of critical conditions in Emergency Departments (ED). This study aimed to describe the EWS assessment results in adult patients at the Emergency Department of RSU Siaga Medika Purbalingga. A descriptive quantitative method with a retrospective approach was used. A total of 338 respondents were selected using Slovin's formula from the population of inpatient ED patients from October to December 2024. Data were collected from medical records and analyzed using univariate analysis. The results showed that most patients were elderly (>60 years old), with a higher proportion of males. The majority of patients had low EWS scores (57.99%) and were categorized in yellow triage (73.37%). These findings indicate that most patients arrived in conditions requiring close monitoring, especially among the elderly group. The study concludes that EWS provides an early clinical overview of patient conditions. It is recommended that hospitals improve training and optimize EWS implementation in the triage process to enhance patient safety and the quality of emergency care services.